Perception on faculty academic relationship management in higher education with reference to self financing engineering colleges - Selvakumar, V.; Maran, K.; Sankar, S. (International Journal of Engineering and Technology, 2017)
The study aims to find out the faculty perceptions in higher education towards academic relationship management. The researcher selected 363 respondents by convenience sampling technique among the faculty members working in engineering colleges in the district of Chennai, Kanchipuram and Thiruvallur districts of Tamilnadu for this study. This study is to find out the perceptional difference in relationship management due to demographic factorsâ€“gender, age, designation and marital status and contributing factors- team work, Job stress and work environment. The study revealed thatÂ major faculty members perceive work environment, teamwork, leadership, career growthÂ are theÂ key dimensions thatÂ has influenceÂ on relationship management if these dimensions are perceived positively. Moreover, job stress has a negative impact on the perception of faculty academic relationship by the faculty members.